2019
DOI: 10.1002/pon.5233
|View full text |Cite
|
Sign up to set email alerts
|

No effect of CBT‐based online self‐help training to reduce fear of cancer recurrence: First results of the CAREST multicenter randomized controlled trial

Abstract: Objective: Fear of cancer recurrence (FCR) is a common consequence of surviving cancer; therefore, easily accessible self-help training could help many cancer survivors deal with FCR at low costs. The CAncer REcurrence Self-help Training (CAREST) trial evaluates the effectiveness of an online-tailored self-help training on the basis of evidence-based cognitive behavioral therapy principles in breast cancer survivors.Also, possible predictors for benefitting from the online self-help training were examined.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…It is possible that patients with a high fear of recurrence are more likely to avoid participation, as it means being confronted with their fear. This is in line with a recent study on online self-help for fear of cancer recurrence that found that most patients do not login or express a need for support [ 45 ]. As fear of recurrence is an unmet need among cancer patients [ 46 ], this group might need more information prior to enrollment in an intervention like eMBCT [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that patients with a high fear of recurrence are more likely to avoid participation, as it means being confronted with their fear. This is in line with a recent study on online self-help for fear of cancer recurrence that found that most patients do not login or express a need for support [ 45 ]. As fear of recurrence is an unmet need among cancer patients [ 46 ], this group might need more information prior to enrollment in an intervention like eMBCT [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Clients mainly suffer from severe cancer-related fatigue, anxiety, trauma, stressrelated and depressive disorders, relationship problems and/or prolonged grief disorder. Since 2009 the institute offers specific internetbased interventions for cancer patients, such as Mindfulness-Based Cognitive Therapy (MBCT) for cancer-related fatigue 1,2 and Anxiety and Depression, 3,4 self-help and blended Cognitive Behavioural Therapy (CBT) for fear of cancer recurrence 5,6 within a secure environment.…”
Section: Video-consultsmentioning
confidence: 99%
“…Web-based interventions have the potential to fill an important gap in quality cancer care by augmenting limited available mental health services [45]. However, there is some evidence that entirely self-guided web-based FCR interventions may have limited efficacy, and it has been suggested that therapist input may increase efficacy [46]. Web-based therapist-guided cognitive therapy has advantages for both patients and providers and effects appear comparable to traditional face-to-face therapy in treating distress in patients with cancer [47,48].…”
Section: Introductionmentioning
confidence: 99%